2007
DOI: 10.1158/1535-7163.mct-06-0231
|View full text |Cite
|
Sign up to set email alerts
|

A novel class of pyranocoumarin anti–androgen receptor signaling compounds

Abstract: Androgen and the androgen receptor (AR) -mediated signaling are crucial for prostate cancer development. Novel agents that can inhibit AR signaling in liganddependent and ligand-independent manners are desirable for the chemoprevention of prostate carcinogenesis and for the treatment of advanced prostate cancer. We have shown recently that the pyranocoumarin compound decursin from the herb Angelica gigas possesses potent anti-AR activities distinct from the anti -androgen bicalutamide. Here, we compared the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
68
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 27 publications
5
68
1
Order By: Relevance
“…For various reasons, the most important of which may be public acceptance, natural products are preferred over synthetic agents for this role. In recent years, much progress has been made in identification of novel prostate cancer chemopreventive and chemotherapeutic agents from natural products (8,9,(26)(27)(28)(29)(30)(31)(32)(33)(34). It should be noted that luteolin and apigenin, two major active compounds of W. chinensis, have been independently reported as having potential for prostate cancer treatment through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For various reasons, the most important of which may be public acceptance, natural products are preferred over synthetic agents for this role. In recent years, much progress has been made in identification of novel prostate cancer chemopreventive and chemotherapeutic agents from natural products (8,9,(26)(27)(28)(29)(30)(31)(32)(33)(34). It should be noted that luteolin and apigenin, two major active compounds of W. chinensis, have been independently reported as having potential for prostate cancer treatment through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, several studies have addressed the effects of decursin and its derivatives on the prevention and mitigation of chronic health disorders. 14 It is well known that coumarin derivatives have estrogenic activity, since they bind to intracellular receptors for estradiol and progesterone.…”
Section: Introduction Dmentioning
confidence: 99%
“…6A), is one of the most prevalent compounds in the roots of Korean A. gigas (Yim et al, 2005). It was suggested previously that the side chain of decursin mediates its anticancer activity against hormone-refractory DU145 prostate cancer cells (Yim et al, 2005), and the side chain of decursin was shown to confer anti-AR activity in LNCaP prostate cancer cells (Guo et al, 2007). In this study, decursinol lacked the properties of decursin; it had no effect on Wnt3aCM-induced CRT, the intracellular ␤-catenin level, or the expression of ␤-catenin-dependent genes in HEK293 reporter and PC3 cells.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that decursin suppresses growth and promotes apoptosis in human prostate carcinoma cells (Yim et al, 2005;Jiang et al, 2006). Moreover, the (CH 3 ) 2 -CϭCH-COO-side chain of decursin, which is replaced with an OH group in decursinol, seems to be necessary for its anticancer activity (Yim et al, 2005;Guo et al, 2007). In the present study, we identified decursin as an inhibitor of the Wnt/␤-catenin pathway using cell-based small-molecule screening.…”
mentioning
confidence: 99%